PENGARUH PENJUALAN TERHADAP LABA BERSIH PADA PERUSAHAAN SUB SEKTOR FOOD AND BEVERAGES YANG TERDAFTAR DI BURSA EFEK INDONESIA - Siti Aisyah Siregar (Fisarrearch, 2022)
Based on the type of problem studied, the research approach used is associative. The data collection technique used is a documentation study by collecting data on the 2015-2019 financial statements. The data analysis technique used in this research is simple linear regression. The results show that sales have a significant effect on net income in food and beverage sub-sector companies listed on the Indonesia Stock Exchange.